Pengaruh Sistem Persediaan Barang terhadap Pengendalian Internal Persediaan Barang: Studi pada salah satu instansi pemerintah daerah di Kabupaten Bandung - Dudi Mustofa; Boy Suzanto; Haris Nurdiansyah; Jimmy Rusjiana (Center of Research, STIE Pasundan, Bandung, Indonesia., 2022)
This study aimed to investigate the effect of the inventory system on internal control. The study used a descriptive and verification approach that was carried out employing a survey of employees at one of the local government agencies in Bandung Regency with 35 respondents. The study results show a robust correlation coefficient between the inventory system and the internal control of the inventory, which is indicated by the coefficient of determination, and the rest is influenced by other factors not examined by the authors in this study. Based on the study results, it is better if there are changes in the inventory system; socialization and evaluation are carried out by communicating systematically to employees so that employees can quickly adapt and understand well. Furthermore, agencies need to hold special training for all employees related to supplies so that productive human resources can be created and optimized for better agencies going forward.